Could Early Modern Messianic Movements Cross Religious Boundaries? - Goldish, Matt (Journal of the economic and social history of the Orient, 2018)
Abstract Could early modern messianic movements cross religious boundaries? Drawing on several examples of Jewish messianic movements from the sixteenth to eighteenth centuries, this paper argues that in certain very specific circumstances they could. The circumstances of such crossover tended to be particular to the early modern period, such as the Converso condition, the participation of Christian Hebraists, and shared messianic expectations among Jews, Christians and Muslims.